The Effect Of Price Discount And Free Gift On Online Entrepreneurs' Business Performance In Social Commerce - Nor Asiah Yaakub; Khalil Md Nor; Ahmad Jusoh (Academia Industry Networks (ACINET), 2024)
Volume: 3 No: 3 (pp.:29-42)